Integrated Adaptation Approaches to Climate Change in Semi-arid Basin of Iran - Solaymani, Hamid R; Gosain, A K (Annals of Arid Zone, 2019)
The major challenges concerning freshwater include: experiencing extremesof too much and/or, too little water, and consequent water issues. Each of theseproblems may be intensified by climate change in semi-arid areas. Existing researchand observational evidence provide strong arguments that future climate may changesignificantly and, therefore, impact the water resources of the Karkheh basin of Iran.Thus, the strategies that can be used to mitigate possible negative impacts of climatechange on water resources are of great importance. The risk of drought and heat stressis expected to increase in the whole of the study area. Overall, the present study showsthe consequences of climate change on the water resources of the Karkheh Basin andshall be useful in formulating the adaptation options in a sustainable manner. SWATmodel was used for impact assessment analysis by using the future climate scenario withfuture regional climate models. It has been found that there shall be an explicit deficitin water as well as crop yield during the end of the century. The impact of suggestedadaptation activities had various effects on hydrology and the same has been depictedthrough tracking major hydrological components; e.g. surface runoff, groundwater andsediment erosion. Amongst the suggested adaptation scenarios, activities that includeterracing, strip cropping, Grade Stabilization Structure (GSS), and contouring werefound to influence the desired hydrologic components significantly. The land use andcropping pattern changes were also successful in bringing about the desired changesto the hydrologic components.Key words: Adaptation, crop pattern, land use, Karkheh Basin, SWAT model.